The discourse on science, Islam and modernity in 19th century thought: Sayid Jamal Al-Din Al-Afghani’s exchange with ernest renan as a casestudy / Fadzlullah bin Shuib - Shuib, Fadzlullah (2012)
The purpose of this dissertation is to describe and contextualize an account of the discourse on modern science, Islam and modernity in the nineteenth century. It is a descriptive and analytic undertaking, written in an academic language.The study is primarily based on the assumption that the current debate on science, Islam and modernity in the the nineteenth century can be presented through the elaboration and analysis of the works of renowned thinkers. The research scope encompasses both Islamic and Western thought in relation to works written by two scholars namely Sayyid Jamal al-Din Al-Afghani and Ernest Renan, as well as examining other scholars’ perspective within the context of civilizational conflicts between the Islamic point of view and the West.Specifically, this project examines the Islamic-Western discourse through the Al-Afghani-Renan exchange in Sorbonne in 1883 as a case study. The exchange constitutes one locus for Muslim and Western intellectuals to reevaluate the meaning and relevance of "science," "Islam," and "modernity" in the context of 19th century thought. The research attempts to elaborate on three philosophical positions within the discourse, which emphasizes on Islamic fundamentalism and the neo-traditionalism led by al-Afghani, as opposed to the rational and liberal tradition of the Enlightenment, the 19th century tradition of Western Positivism, neo-Enlightenment and Liberalism, as presented by Renan. Each thinker offers differing answers to fundamental questions surrounding the discourse. For instance, Renan viewed Islam as a Semitic religion and Arabs as a Semitic race, where both were deemed incapable to make any meaningful contribution to the growth of science and philosophy. He was also convinced that the Semitic Oriental sensibility never reached the heights attained by the Indo-Germanic races. And what is commonly known as ‘Arab’ science and philosophy was actually contributed by the Greeks and Persians. Renan’s arguments are buttressed by the Orientalist theory of origins, viz., which popularize the position of the Indo-European race as the source of science and philosophy. On the ground, the debates between al-Afghani and Renan on science, Islam and modernity in 19th century perspective have been turned into philosophical debates by intellectuals. The most significant conclusion is that after highlighting the regenerative role of Islam in nurturing science and philosophy, al-Afghani concluded that religions, by whatever names they are called, bear similarities. There are no two ways with regard to religion and science. Religion, especially Islam, imposes on man its sets of rules and beliefs, whereas philosophy and science free him, be it in total or partially. Al-Afghani’s reconciliation of science and Islam as illustrated in his response was within the predominant neo-revivalist and neo-traditionalist attempt to create political consciousness to free Muslims from foreign interference. Al-Afghani’s efforts at reconciling science with Islam were grounded in this framework.